Role of antioxidants in the protection against the combined effect of Cd, Zn, and Ni in wheat - Gryshko, V. M.; Artiushenko Т. А.; Boldizsґar A.; Kocsy, G. (Reports of the National Academy of Sciences of Ukraine, 2016)
The effect of the combined treatment with Cd, Zn, and Ni on the accumulation of these metals, growth, and contents of antioxidants in wheat roots is studied. The metals were added in two concentrations to the nutrient solution for seedlings, and the higher one had a stronger effect on the studied parameters. The heavy-metal tolerances of 8 wheat varieties are compared in order to select the most tolerant (Kuial’nik) and most sensitive one (Sonechko) for biochemical studies. The heavy-metal uptake and, subsequently, the lipid peroxidation are smaller in the tolerant genotype, than in the sensitive one. The higher glutathione concentration in the tolerant genotype under control conditions could contribute to the improved heavy-metal tolerance. The metal-induced decrease in the glutathione content can be an indicator of the increased phytochelatin synthesis. The great tolerance of Kuial’nik can be explained by its decreased heavy-metal uptake and the greater glutathione-based antioxidant capacity.